Advancement Strategy for Economic Value Malay Cultural Arts to Welcome the Industrial Revolution 4.0: Performing Arts, Literature, History, and Archeology - Mahdi Bahar (Proceeding International Conference on Malay Identity, 2020)
Malay cultural art is an asset and potential that can be made of economic value. Basically, the existence of cultural arts is only attached or attached by the conventions of the supporting community, so that the entity is in a socio-cultural context. In order to have economic value, it definitely requires 'processing' as a strategy. Inherent here is the persistence of the existence of Malay art and culture not only attached by convention factors related to tradition or custom alone (socio-cultural), but also by artistic factors so that they are needed (economic value), especially as a tourism industry. Contained in this sense is the existence of processing (transformation) which is oriented towards taking the role as a subject in change. The consequence is that the activity or creativity of Malay art and culture should be addressed to meet needs, both needs that have been created, as well as creating needs that did not exist before, for example, products of advancement in technology. Keywords: Strategy; advancement; art; Malay culture; industrial revolution 4.0